Development of an Integrated Helminthiasis Prevention Education Model in Elementary Schools: Utilizing Picture Storybooks and Storytelling as Learning Media - Armaidi Darmawan; Ahmad Syauqy; Andika Sulistiawan; Wahyu Indah Dewi Aurora; Erny Kusdiyah (Postgraduate, University of Mataram, 2025)
Helminthiasis remains a significant health issue, especially in developing countries like Indonesia, where the prevalence among elementary school children ranges from 31.8% to 80%, particularly in areas with poor sanitation. This condition can cause anemia, malnutrition, cognitive impairment, and reduced academic performance. Therefore, an effective school-based prevention model is necessary. This study aimed to develop and evaluate an educational model for helminthiasis prevention using picture storybooks and storytelling. A mixed-methods approach was used, involving qualitative validation by experts and quantitative analysis through pre- and post-tests. A total of 100 respondents, including teachers, parents, and health officers, participated in a survey assessing their knowledge of helminthiasis prevention and school sanitation conditions. The effectiveness of the educational intervention was analyzed using paired t-tests. Results showed that majority of 70% of respondents are aware of helminthiasis. Regarding school sanitation, 55% of respondents disagree that the sanitation in elementary schools is adequate. Statistical analysis indicated a significant improvement in students' understanding post-intervention (t = 16.65, p = 0.002). This study confirms that picture storybooks and storytelling effectively enhance students’ awareness and understanding of helminthiasis prevention. Further research is recommended to evaluate the long-term impact of this intervention.